Salivary duct carcinoma with rhabdoid features: Report of 2 cases with immunohistochemical and ultrastructural analyses. Issue 3 (17th December 2013) - Kusafuka, Kimihide; Onitsuka, Tetsuro; Muramatsu, Koji; Miki, Tomoko; Murai, Chika; Suda, Toshihito; Fuke, Tomohito; Kamijo, Tomoyuki; Iida, Yoshiyuki; Nakajima, Takashi; Andersen, Peter
Abstract Background Salivary duct carcinoma with rhabdoid features is extremely rare. Methods We report 2 cases of salivary duct carcinoma with rhabdoid features treated at our institution. Results Case 1 was a 44‐year‐old Japanese man who had swelling in the left parotid region. This tumor consisted of residual pleomorphic adenoma and widely invasive carcinoma, which showed a diffuse growth pattern by atypical rhabdoid cells. Case 2 was a 66‐year‐old Japanese man who had swelling of the right cervical region. This submandibular tumor was also composed of both residual pleomorphic adenoma region and invasive adenocarcinoma components, whereas some metastatic lesions were purely composed of rhabdoid cells. Such cells were strongly and diffusely positive for cytokeratins (CKs), gross cystic disease fluid protein‐15 (GCDFP), and androgen receptor (AR). Case 1 was also positive for Her‐2 and p53. Conclusion Both patients were diagnosed with carcinoma ex pleomorphic adenoma and their carcinomatous components were composed of salivary duct carcinoma with rhabdoid features, which is a highly aggressive tumor, similar to salivary duct carcinoma. © 2013 The Authors. Head & Neck published by Wiley Periodicals, Inc. Head Neck36: E28–E35, 2014